The Impact of Micro-Learning on Social Media in Design: Enhancing Creative Skills and Design Techniques through Digital Platforms (المجلة الدولية للبحوث العلمية, 2025)
This study examines the transformation of microlearning for creative and design practice skills in design students. This study examines the potential influence of short-form, ‘snackable’ content via platforms such as TikTok, Instagram, and YouTube. This study relies on the Cognitive Load Theory, as a theoretical framework which introduced by John Sweller, the theory suggests that working memory can only handle a limited amount of information at a time. The research design is qualitative approach, with 90 students surveyed and a corresponding analysis of the content of 15 short educational videos. The survey findings revealed a strong preference for microlearning, as 80 percent of the respondents perceived it to be effective and engaging. There are some broader implications, too: Content analysis also reveals that videos shorter than a minute that feature either voiceover or context-embedded text are the most engaging and educationally effective. The authors imply that microlearning can contribute to knowledge recall and activity engagement, innovation, and creativity, and thus serves as a supplementary or alternative method to traditional design education. Suggestions for educators and creators to take advantage of platform evolving trends in relation to learning gains are presented.